On the provenance of a historic sledge shoe fragment, said to have been collected by Edward Wilson at the South Pole in 1912 - Rowe, RSW (Cambridge University Press, 2017)
This paper discusses the authentication of a metal sledge shoe fragment, believed by the owner to have been collected by Edward Wilson close to the South Pole on 18 January 1912. Microscopic and elemental analysis show that the object is made from ‘German silver’, a copper alloy used only on Norwegian Nansen-style sledges in the late nineteenth and early twentieth century, and that it was used to clad a tapering sledge runner end about 10 mm thick. By comparing related objects, including sledges used by Amundsen and Scott in their South Pole journeys and a sledge from the Discovery Expedition, we show that the object cannot have come from an English sledge, but would have fitted one of Amundsen's modified sledges. Written sources have been extensively searched, but no direct written provenance for the object exists. However, contemporary Norwegian and British accounts explain specific features of the object and exclude other possible provenances. We conclude that it is most likely that the proposed provenance and history attached to this artefact are correct. The author is supported by the United Kingdom Antarctic Heritage Trust. The research received no specific grant from any funding agency, commercial or not-for-profit sectors.